2018
DOI: 10.1101/405076
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

On the role of different age groups during pertussis epidemics in California, 2010 and 2014

Abstract: Background: There is limited information on the roles of different age groups in propagating pertussis outbreaks, and the temporal changes in those roles since the introduction of acellular pertussis vaccines.Methods: The relative roles of different age groups in propagating the 2010 and the 2014 pertussis epidemics in California were evaluated using the RR statistic that measures the change in the group's proportion among all detected cases before-vs.-after the epidemic peak.

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 24 publications
1
9
0
Order By: Relevance
“…However, the coefficient for delay × age group 13–18 years was negative meaning a temporal decline in titres for participants aged 13–18 years, suggesting that those adolescents played a disproportionate role in propagating the epidemic. The latter would be consistent with previous studies [ 25 , 26 ]. Besides, various models studying the immune response to B. pertussis infection provided evidence that secondary exposure is less likely to boost immunity than primary exposure, given equal levels of contact with B. pertussis .…”
Section: Discussionsupporting
confidence: 94%
“…However, the coefficient for delay × age group 13–18 years was negative meaning a temporal decline in titres for participants aged 13–18 years, suggesting that those adolescents played a disproportionate role in propagating the epidemic. The latter would be consistent with previous studies [ 25 , 26 ]. Besides, various models studying the immune response to B. pertussis infection provided evidence that secondary exposure is less likely to boost immunity than primary exposure, given equal levels of contact with B. pertussis .…”
Section: Discussionsupporting
confidence: 94%
“…The role of different age groups during the subsequent waves of Omicron epidemics is less studied. In this paper, we applied the previously developed methodology [8][9][10]3,4] to study the relative role of individuals in different age groups during the Spring, Summer, and Autumn waves of the Omicron epidemics in France. We found that children aged 10-19y played the greatest relative role in propagating Omicron epidemics, particularly when schools were open, followed by children aged 0-9y and adults aged 20-29y, as well as adults aged 30-49y.…”
Section: (Which Was Not Certified By Peer Review) Preprintmentioning
confidence: 99%
“…In [14][15][16] we developed a method for assessing the relative role (per average individual) in different subpopulations in the spread of infection during epidemics of infectious diseases. The idea of that method is that subpopulations that play a disproportionate role during the outbreak's ascent due to increased susceptibility to infection and/or contact rates can be related to the relative risk (RR) statistic that evaluates the change in the subpopulation's proportion among all cases in the population before vs. after the epidemic's peak (see Methods).…”
Section: Introductionmentioning
confidence: 99%
“…Less is known about the contribution of different age groups to the spread of infection during the subsequent waves of the Omicron epidemic. In this paper, we used the previously developed methodology [3,4,[21][22][23] ascent period of the epidemic in children aged 5-14y, followed by children aged 0-4y and 15-19y. This result is generally in agreement with the findings in our study of Omicron epidemics in France [14], as well as with the high rates/earlier peaks of infection in children in England in the UK coronavirus survey data for that period [9].…”
Section: Discussionmentioning
confidence: 99%
“…In our earlier work [21][22][23] we introduced a method for evaluating the role of individuals in different population groups in the spread of infection and applied it to data from epidemics associated with influenza, respiratory syncytial virus (RSV) and pertussis in the United States.…”
Section: Introductionmentioning
confidence: 99%